Country stereotypes in consumer judgemental strategies : effects of cue incongruity and product knowledge. - Lye, Kah Hou. (2009)
Marketing practitioners and researchers have long observed the influence of extrinsic product cues on consumer behaviour. In today's globalized marketplace, country-of-origin and brand name are two cues that have considerable influence on the consumer. As a result of multinational production and international marketing, "hybrid" or "binational" products that involve two countries-of-origin are commonly found in the marketplace now. The impact on consumer judgement of products that carry brand names associated with one country but are manufactured in another thus warrants further study.